PEREMPUAN BERKALUNG SORBAN: RESISTANCE TOWARD PATRIARCHY SYSTEM IN THE SPACE OF TRADITION OF PESANTREN IN EAST JAVA - Aquari Mustikawati (Pusbindiklat - LIPI, 2011)
Abidah El Khalieqy is known as a writer with feminism concept. She tries to deconstruct patriarchy system. In her novel Perempuan Berkalung Sorban, she reflects differences of gender discrimination in pesantren community. This research tries to reveal woman resistances toward patriarchy system in the space of tradition and pesantren of the novel. To analize data of the research, qualitative approach and descriptive method are used. The resistance indicates that patriarchy system in tradition space and pesantren space are women’s rights problems to equal with men.